Proximal Arch in Left Thoracotomy Repair of Neonatal and Infant Coarctation—How Small Is Too Small?. Issue 4 (July 2019) - Callahan, Connor P.; Saudek, David; Creighton, Sara; Kuhn, Evelyn M.; Mitchell, Michael E.; Tweddell, James S.; Woods, Ronald K.
Background: We sought to evaluate the relationship between proximal arch hypoplasia and reintervention for left thoracotomy repair of coarctation of the aorta. Methods: This was a retrospective review of 153 consecutive neonates and infants undergoing left thoracotomy and extended end-to-end repair of coarctation from January 1, 2000, to January 1, 2014, at a single center with exclusion of single ventricle–palliated patients. Primary outcome was reintervention evaluated with respect to five definitions of proximal arch hypoplasia. Results: Median follow-up was 7.2 years. Reintervention occurred in eight (5.2%) patients, with 50% of patients undergoing re-intervention in the first six months after their index operation. Using Kaplan-Meier analysis and log-rank test, with hypoplasia defined by weight, hypoplasia was not associated with increased reintervention for arch size < patient weight (in kilograms; P = .24) or for arch size < patient weight (in kilograms) +1 ( P = .02, higher freedom from reintervention in hypoplasia group). For each of the five comparison groups, freedom from reintervention was similar between the groups with and without proximal arch hypoplasia: (1) z -score < −2 versus ≥−2 ( P = .72), (2) z -score < −3 versus ≥−3 ( P = .95), and (3) z -score < −4 versus ≥−4 ( P = .17). Conclusion: In our cohort of patients with left thoracotomy and extended end-to-end repair of coarctation, proximal arch hypoplasia, defined by various weight-based or z -score thresholds, was not associated with reintervention. While this may imply value to a more liberal use of thoracotomy, confirmation requires longer term follow-up with a more comprehensive evaluation of the patients and their arches.